The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Etiology and Morphogenesis of Congenital Heart Disease 2016
DOI: 10.1007/978-4-431-54628-3_21
|View full text |Cite
|
Sign up to set email alerts
|

TMEM100: A Novel Intracellular Transmembrane Protein Essential for Vascular Development and Cardiac Morphogenesis

Abstract: Among members of the TGFβ superfamily, bone morphogenetic protein (BMP) 9 and BMP10 regulate vascular endothelium differentiation and morphogenesis by activating the specific receptor complex, which consists of ALK1 (or ACVRL1), BMPR2, and endoglin. Mutations in ACVRL1, BMPR2, or ENG are associated with hereditary hemorrhagic telangiectasia and pulmonary arterial hypertension in humans [1, 2]. We previously identified TMEM100 as a downstream target gene of BMP9/BMP10-ALK1 signaling pathway [3]. TMEM100 is a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Moreover, ablation of the complex in spinal cord central terminals produced more pronounced anti-hypersensitivity than disruption of the complex in hind paws. 60,61 Alteration of sensitization levels within the A1-V1 complex could occur in two ways: activity dependent and activity independent. This implies that the reduction of sensitization occurs by attenuating neurotransmission at presynaptic levels more than by lowering receptor potentials in peripheral terminals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ablation of the complex in spinal cord central terminals produced more pronounced anti-hypersensitivity than disruption of the complex in hind paws. 60,61 Alteration of sensitization levels within the A1-V1 complex could occur in two ways: activity dependent and activity independent. This implies that the reduction of sensitization occurs by attenuating neurotransmission at presynaptic levels more than by lowering receptor potentials in peripheral terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Second, ablation or inhibition of Tmem100 could lead to significant side effects since it is critically important in other tissues. 60,61 Alteration of sensitization levels within the A1-V1 complex could occur in two ways: activity dependent and activity independent. Activity-dependent interactions between TRPA1 and TRPV1 channels often require sequential stimulation of TRPA1 and TRPV1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study showed that overexpression of TMEM100 did not affect the EC cellular barrier integrity under the Thrombin challenge 13 , suggesting that the regulation of vascular permeability by Tmem100 in vivo might be due to the indirect regulation of extracellular matrix but not EC junction. In another study, Somekawa et al showed that Tmem100 null embryos showed fetal defects of arterial endothelium differentiation and severe vascular dysmorphogenesis and cardiac enlargement at E9.5 and massive pericardial effusion and growth retardation at E10.5 11,18 . These phenotypes are identical to the Acvrl1 deficiency mice 20 .…”
Section: Role Of Tmem100mentioning
confidence: 98%
“…As a downstream target of the Bone Morphogenetic Protein (BMP) 9/10 and Activin-Like Kinase Receptor Type I (ALK1) signaling pathways 18 , TMEM100 plays an important role in angiogenesis, vascular morphogenesis, integrity and cardiovascular development. BMP9/10 acts mainly via an EC-specific ALK1 receptor and promote arterial endothelial maturation and quiescence.…”
Section: Role Of Tmem100mentioning
confidence: 99%